WHO/ILO work-related burden of disease and injury: Protocol for systematic reviews of exposure to occupational ergonomic risk factors and of the effect of exposure to occupational ergonomic risk factors on osteoarthritis of hip or knee and selected other musculoskeletal diseases. (April 2019) - Hulshof, Carel T.J.; Colosio, Claudio; Daams, Joost G.; Ivanov, Ivan D.; Prakash, K.C.; Kuijer, Paul P.F.M.; Leppink, Nancy; Mandic-Rajcevic, Stefan; Masci, Frederica; van der Molen, Henk F.; Neupane, Subas; Nygård, Clas-Håkan; et al.
Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing a joint methodology for estimating the national and global work-related burden of disease and injury (WHO/ILO joint methodology), with contributions from a large network of experts. In this paper, we present the protocol for two systematic reviews of parameters for estimating the number of disability-adjusted life years from osteoarthritis of hip or knee, and selected other musculoskeletal diseases respectively, attributable to exposure to occupational ergonomic risk factors to inform the development of the WHO/ILO joint methodology. Objectives: We aim to systematically review studies on exposure to occupational ergonomic risk factors (Systematic Review 1) and systematically review and meta-analyze estimates of the effect of exposure to occupational ergonomic risk factors on osteoarthritis of the hip or knee, and selected other musculoskeletal diseases respectively (Systematic Review 2), applying the Navigation Guide systematic review methodology as an organizing framework, conducting both systematic reviews in tandem and in a harmonized way. Data sources: Separately for Systematic Reviews 1 and 2, we will search electronic academic databases for potentially relevant records from published and unpublished studies, including Medline, EMBASE, Web of Science and CISDOC. We will also search electronic grey literature databases, Internet search engines and organizational websites; hand-search reference lists of previous systematic reviews and included study records; and consult additional experts. Study eligibility and criteria: We will include working-age (≥15 years) workers in the formal and informal economy in any WHO and/or ILO Member State, but exclude children (<15 years) and unpaid domestic workers. The included occupational ergonomic risk factors will be any exposure to one or more of: force exertion; demanding posture; repetitiveness; hand-arm vibration; lifting; kneeling and/or squatting; and climbing. Included outcomes will be (i) osteoarthritis and (ii) other musculoskeletal diseases (i.e., one or more of: rotator cuff syndrome; bicipital tendinitis; calcific tendinitis; shoulder impingement; bursitis shoulder; epicondylitis medialis; epicondylitis lateralis; bursitis elbow; bursitis hip; chondromalacia patellae; meniscus disorders; and/or bursitis knee). For Systematic Review 1, we will include quantitative prevalence studies of any exposure to occupational ergonomic risk factors stratified by country, gender, age and industrial sector or occupation. For Systematic Review 2, we will include randomized controlled trials, cohort studies, case-control-studies and other non-randomized intervention studies with an estimate of the relative effect of any exposure with occupational ergonomic risk factors on the prevalence or incidence of osteoarthritis and/or selected musculoskeletal diseases, compared with the theoretical minimum risk exposure level (i.e., no exposure). Study appraisal and synthesis methods: At least two review authors will independently screen titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. At least two review authors will assess risk of bias and the quality of evidence, using the most suited tools currently available. For Systematic Review 2, if feasible, we will combine relative risks using meta-analysis. We will report results using the guidelines for accurate and transparent health estimates reporting (GATHER) for Systematic Review 1 and the preferred reporting items for systematic reviews and meta-analyses guidelines (PRISMA) for Systematic Review 2. PROSPERO registration number: CRD42018102631. Highlights: WHO and ILO are developing a joint methodology for estimating the national and global work-related burden of disease and injury. This article presents a protocol for two systematic reviews for the development of this WHO/ILO joint methodology. Prevalence studies on exposure to occupational ergonomic risk factors will be systematically reviewed. Studies on effects of occupational ergonomic risk factor exposure on selected musculoskeletal diseases will be systematically reviewed and meta-analysed.